Efficacy of quadruple treatment on different types of pre‐operative anaemia: secondary analysis of a randomised controlled trial. (27th April 2020) - Rössler, J.; Hegemann, I.; Schoenrath, F.; Seifert, B.; Kaserer, A.; Spahn, G. H.; Falk, V.; Spahn, D. R.
Summary: In patients with pre‐operative anaemia undergoing cardiac surgery, combination treatment with intravenous iron, subcutaneous erythropoietin alpha, vitamin B12 and oral folic acid reduces allogeneic blood product transfusions. It is unclear if certain types of anaemia particularly benefit from this treatment. We performed a post‐hoc analysis of anaemic patients from a randomised trial on the 'Effect of ultra‐short‐term treatment of patients with iron deficiency or anaemia undergoing cardiac surgery'. We used linear regression analyses to examine the efficacy of a combination anaemia treatment compared with placebo on the following deficiencies, each representing a part of the combination treatment: ferritin and transferrin saturation; endogenous erythropoietin; holotranscobalamine; and folic acid in erythrocytes. Efficacy was defined as change in reticulocyte count from baseline to the first, third and fifth postoperative days and represented erythropoietic activity in the immediate peri‐operative recovery phase. In all 253 anaemic patients, iron deficiency was the most common cause of anaemia. Treatment significantly increased reticulocyte count in all regression analyses on postoperative days 1, 3 and 5 (all p < 0.001). Baseline ferritin and endogenous erythropoietin were negatively associated with change in reticulocyte count on postoperative day 5, with an unstandardised regression coefficient B of −0.08 (95%CI −0.14 to −0.02) and −0.14 (95%CI −0.23 to −0.06), respectively. Quadruple anaemia treatment was effective regardless of the cause of anaemia and its effect manifested early in the peri‐operative recovery phase. The more pronounced a deficiency was, the stronger the subsequent boost to erythropoiesis may have been.